2014
DOI: 10.1631/jzus.b1300238
|View full text |Cite
|
Sign up to set email alerts
|

Aroma changes of black tea prepared from methyl jasmonate treated tea plants

Abstract: Methyl jasmonate (MeJA) was widely applied in promoting food quality. Aroma is one of the key indicators in judging the quality of tea. This study examined the effect of exogenous MeJA treatment on tea aroma. The aroma components in black tea prepared from MeJA-treated fresh tea leaves were extracted using headspace solid-phase microextraction (HS-SPME) and were analyzed using gas chromatography-mass spectrometry (GC-MS) and GC-olfactometry (GC-O). Forty-five volatile compounds were identified. The results rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
3
27
0
Order By: Relevance
“…4‐Hydroxy‐2,5‐dimethyl‐3(2 H )‐furanone had a significant influence on the ‘sweet’ aroma, followed by ( E )‐2‐hexenal, dodecanal, β ‐myrcene, α ‐farnesene, and nerolidol. 1‐Octen‐3‐ol, which contributed significantly to the ‘woody and mushroom‐like’ smell, had the highest negative coefficient (−1.76) . Methyl jasmonate, which has a ‘floral’ smell, is well known, as it could improve the aroma quality of agricultural products such as tea, fruits, and vegetables .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4‐Hydroxy‐2,5‐dimethyl‐3(2 H )‐furanone had a significant influence on the ‘sweet’ aroma, followed by ( E )‐2‐hexenal, dodecanal, β ‐myrcene, α ‐farnesene, and nerolidol. 1‐Octen‐3‐ol, which contributed significantly to the ‘woody and mushroom‐like’ smell, had the highest negative coefficient (−1.76) . Methyl jasmonate, which has a ‘floral’ smell, is well known, as it could improve the aroma quality of agricultural products such as tea, fruits, and vegetables .…”
Section: Resultsmentioning
confidence: 99%
“…Among the three major kinds of tea (black, green, and oolong), black tea accounts for approximately 75% of the world's tea trade . Congou black tea, which originated in China, is the oldest black tea in the world and has been well known for centuries, such as Keemun black tea and Dianhong black tea . By using the orthodox method, which includes withering, rolling, fermentation, and firing, Congou black tea has a more complete shape and a lower degree of oxidation of phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is reasonable to draw a conclusion that the content changes of the volatile constituents were resulted from the enzymatic treatment. It has been reported that geraniol could be generated via the catalysis of geraniol synthase and β‐glucosidase (Ho, Zheng, & Li, ; Su, Xia, Gao, Dai, & Zhang, ); benzaldehyde might come from the oxidative degradation of amino acids (Ho et al, ); phenylethyl alcohol could be generated by the enzymatic hydrolysis of its glycoside precursors (Shi et al, ); and β‐ trans‐ damascenone might result from the transformation of glycoconjugate precursors at high temperatures during the manufacturing of tea leaves (Kinoshita et al, ). In addition, the contents of benzaldehyde and phenylethyl alcohol have been observed to increase after the combined treatment of laccase and α‐galactosidase (Zhang & Du, ).…”
Section: Resultsmentioning
confidence: 99%
“…Jasmonates influence the coordinated expression of numerous genes encoding key enzymes in plant secondary metabolic pathways, thus affecting the accumulation of plant secondary metabolites at the transcription level (Vom Endt, Soares e Silva, Kijne, Pasquali, & Memelink, ). MeJA has also been reported to improve the aroma quality of black tea clearly (Shi et al., ). When plants are subjected to low‐temperature stress, a series of physiological and biochemical changes occur accompanied by increasing levels of jasmonates.…”
Section: Resultsmentioning
confidence: 99%